Social, cultural, and behavioral modeling : 12th International Conference, SBP-BRiMS 2019, Washington, DC, USA, July 9-12, 2019, Proceedings /: 12th International Conference, SBP-BRiMS 2019, Washington, DC, USA, July 9-12, 2019, Proceedings. (2019) - Unknown
No abstract available